Pengaruh Rasio Profitabilitas, Leverage dan Kebijakan Dividen Terhadap Nilai Perusahaan Studi Pada Sektor Perbankan Di Bursa Efek Indonesia - Ida Ayu Dinda Priyanka Maharani (UNHI Press, 2021)
This study discusses the relationship between profitability ratios, leverage and dividend policy on firm value in the banking sector on the Indonesia Stock Exchange. The banking sector was chosen because the banking sector is one of the fastest growing sectors and has promising long-term business prospects. The high value of the company will affect the level of prosperity of shareholders. Several factors affect firm value, namely profitability, leverage, and dividend policy, which are factors that can be controlled by the company. This study uses Dividend Irrelevance Theory and Bird in The Hand Theory as the main theory in explaining the importance of profitability ratios, leverage ratios and dividend policies in increasing firm value. The analysis technique uses the Path Analysis estimation technique. The results of the study found that leverage has a negative and significant effect on firm value and leverage has a negative effect on dividend policy.